GRAPH MANAGEMENT SYSTEMS: A QUALITATIVE SURVEY - Nolé, Maurizio; Sartiani, Carlo (APTIKOM Publisher, 2020)
In the recent years many real-world applications have been modeled by graph structures (e.g., social networks, mobile phone networks, web graphs, etc.), and many systems have been developed to manage, query, and analyze these datasets. These systems could be divided into specialized graph database systems and large-scale graph analytics systems. The first ones consider end-to-end data management issues including storage representations, transactions, and query languages, whereas the second ones focus on processing specific tasks over large data graphs. In this paper we provide an overview of several  graph database systems and graph processing systems, with the aim of assisting the reader in identifying the best-suited solution for her application scenario.